Navigation and closed-loop control of magnetic microrobot in plant vein mimic environment - Huan, Zhijie; Wang, Jiamin; Zhu, Lan; Zhong, Zhixiong; Ma, Weicheng; Chen, Zhoufan (Frontiers in Plant Science, 2023)
In recent years, research on the control of micro-robots has gradually matured. The motion navigation of micro-robots has also become an important research topic. However, in practice, the micro-robot will be disturbed by the flowing liquid when it moves in the micro-fluid environment. As a result, the trajectory will deviate from the intended trajectory. In this paper, different algorithms for the navigation of the micro-robot in a simulated plant leaf vein environment are investigated. Based on the simulation results, RRT*-Connect is selected as the path planning algorithm after comparing the performance. Based on the pre-planned path, a fuzzy PID controller is designed for precise trajectory tracking, which can effectively eliminate the random disturbance caused by micro-fluid flow during the motion and make it quickly recover to a stable movement state.